Planning in the fertilization of the pineapple cultivation. An analysis of vulnerability (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
The purpose of this research was to analyze the fertilization planning process of the pineapple crop (Ananás comosus) in the El Tequere sector of the Aguedo Felipe Alvarado parish in the Iribarren municipality of Lara State. Framed under a field design of a descriptive type and considering as a population object of study all the producers that are located in the sector, the information necessary for the development of the research was obtained by means of the application of a Likert scale questionnaire, highlighting data of interest with which it was possible to describe, diagnose and perform a vulnerability analysis of the fertilization planning process of the aforementioned area. The analysis revealed that this process is performed empirically by people who are not trained to carry out such an important function effectively; Likewise, it showed how 6 of the 10 success factors, considered to be determinant in terms of their influence on the evaluated process, are located in the quadrants I Defenseless and Vulnerable IV, as a result of the low response capacity of the producers to resist and recover. in situations where the shortage of fertilizers, loss of tradition in the production of this item in the area, absence of technical advisors and low prices of final products are the protagonists.
Keywords: planning; fertilization; vulnerability analysis